Upaya Meningkatkan Hasil Belajar Siswa dengan Metode Montessori pada Mata Pelajaran IPA Kelas V Madrasah Ibtidaiyah - Ummu Jauharin Farda; Esty Cahyaningsih (Departement of Mathematics Education, 2023)
The background of this classroom action research is the low learning outcomes of students at MI NU Tarbiyatuth Thullab Payaman. There are still many students who score below the minimum completeness criteria (KKM). Learning at MI NU Tarbiyatuth Thullab uses conventional methods and is based on teacher center learning so that children often feel bored and bored. Therefore, researchers contribute ideas and innovate learning by using the Montessori method in learning science. The purpose of this study was to find out whether there was an increase in learning outcomes in the science subject for fifth grade students at MI NU Tarbiyatuth Thullab Payaman Mejobo Kudus for the 2021/2022 academic year using the Montessori method. This study used a classroom action research design with 2 cycles, each cycle carried out in four stages, namely planning, implementing, observing, and reflecting. The results of this study indicate a significant increase in the learning outcomes of fifth grade students at MI NU Tarbiyatuth Thullab Payaman Mejobo Kudus for the 2021/2022 academic year in science subjects using the Montessori method. The research data shows that the average score of student learning outcomes increased from 67, 73, 84 with the percentage of completeness in classical learning reaching 88% in the second cycle stage, which was only 73% in the first cycle and 42% in the pre-cycle stage. While the activeness of students in cycle II reached 86% from the previous one which only reached 75%.